Influence of Photography and Graphic Design on the Maintenance of Sales in the Nation and the Sun Newspapers in Osun State - TALABI, Felix Olajide; OGAH, Abari Ijuo; BELLO, Samson Adedapo; OKUNADE, Joshua Kayode; SANUSI, Bernice Oluwalanu; ZANNU, Prosper Nunayon (Journal of Ecohumanism, 2024)
Photographic design plays an essential role in raising awareness towards the sales of newspaper and maintaining the high volume of newspaper sales. This study investigates the influence of photography and graphic design on the maintenance of sales of two newspapers, The Nation and The Sun newspapers in Osun State. Focus group discussion was adopted to investigate the study while pleasure theory, perception theory were used as the theoretical framework. The study focuses on buyers of The Nation and Sun newspapers with a total of 75 respondents in Ede Osun State. Taro Yamane formula sampling technique was used to select 109 readers. Based on the findings, the study recommended that media outlets should review the literature to know the reasons for low patronage and lack of sales so that they can improve on newspaper production to ensure that readers are attracted to newspaper buying. The study recommends that prominence should be given to picture usage on the front page of newspapers because it is the first page that passers-by see to determine the newspaper purchase.